2017
DOI: 10.1007/s12274-017-1472-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting orthotopic gliomas with renal-clearable luminescent gold nanoparticles

Abstract: A major clinical translational challenge in nanomedicine is the potential of toxicity associated with the uptake and long-term retention of non-degradable nanoparticles (NPs) in major organs. The development of inorganic NPs that undergo renal clearance could potentially resolve this significant biosafety concern. However, it remains unclear whether inorganic NPs that can be excreted by the kidneys remain capable of targeting tumors with poor permeability. Glioblastoma multiforme, the most malignant orthotopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 48 publications
0
55
0
Order By: Relevance
“…Compared to other types of dendrimers injected via tail vein in flank tumor models, our hydroxyl‐terminated PAMAM dendrimer results exhibit similar levels of tumor accumulation despite needing to overcome physical transport barriers in orthotopic brain tumors that flank tumors lack 49‐51 . Compared to other types of nanoparticles explored in orthotopic brain tumors, G6 shows a ~100‐fold greater in tumor accumulation than liposomal 52 nanoparticles and ~10‐fold greater than G4 and reported tumor levels of gold 53,54 and PEGylated iron oxide 55 nanoparticles. Studies based on traditional polymeric nanoparticles with ~135 nm size showed only a 50% improvement in the delivery of temozolomide in a rat brain tumor model 56 .…”
Section: Discussionmentioning
confidence: 70%
“…Compared to other types of dendrimers injected via tail vein in flank tumor models, our hydroxyl‐terminated PAMAM dendrimer results exhibit similar levels of tumor accumulation despite needing to overcome physical transport barriers in orthotopic brain tumors that flank tumors lack 49‐51 . Compared to other types of nanoparticles explored in orthotopic brain tumors, G6 shows a ~100‐fold greater in tumor accumulation than liposomal 52 nanoparticles and ~10‐fold greater than G4 and reported tumor levels of gold 53,54 and PEGylated iron oxide 55 nanoparticles. Studies based on traditional polymeric nanoparticles with ~135 nm size showed only a 50% improvement in the delivery of temozolomide in a rat brain tumor model 56 .…”
Section: Discussionmentioning
confidence: 70%
“…In 2013, through a comprehensive comparison of the passive tumor targeting of renal‐clearable NIR‐emitting GS‐AuNPs and a renal clearable organic dye, IRDye 800CW, we found that the EPR effect can still be retained in renal clearable GS‐AuNPs, which exhibited a much longer tumor retention time and faster normal tissue clearance than IRDye 800CW . Through the EPR effect, renal clearable GS‐AuNPs can target different types of cancers, including breast, prostate, and brain cancers (Figure and Table S8).…”
Section: Interactions With Tissues and Organsmentioning
confidence: 98%
“…Reproduced with permission from Ref. . Copyright 2017, Tsinghua University Press and Springer‐Verlag Berlin Heidelberg.…”
Section: Interactions With Tissues and Organsmentioning
confidence: 99%
“…Minireviews and ar enal clearable organic dye,I RDye 800CW,w ef ound that the EPR effect can still be retained in renal clearable GS-AuNPs,which exhibited amuch longer tumor retention time and faster normal tissue clearance than IRDye 800CW. [35] Through the EPR effect, renal clearable GS-AuNPs can target different types of cancers,i ncluding breast, [35,[37][38]47] prostate, [57] and brain cancers [73] (Figure 10 and Table S8).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Reproducedw ith permission from Ref. [73].C opyright 2017, Tsinghua UniversityP ress and Springer-Verlag Berlin Heidelberg. D) The linear relationship between tumor-targeting efficiencies of gold clusters in xenograft model of MCF-7 at 24 hp.i.…”
Section: Tumor Vasculature and Acidity Effectsmentioning
confidence: 99%